Dynamic Scoring: An Introduction to the Issues - Auerbach, Alan J (American Economic Review, 2005)
The controversy over dynamic scoring in the United States is not new.1 But the possibility that dynamic scoring might be adopted has moved closer to reality recently, with initial attempts by